Radical cystectomy or bladder preservation with radiochemotherapy in elderly patients with muscle-invasive bladder cancer: Retrospective International Study of Cancers of the Urothelial Tract (RISC) Investigators. (3rd April 2018) - Boustani, Jihane; Bertaut, Aurélie; Galsky, Matthew D.; Rosenberg, Jonathan E.; Bellmunt, Joaquim; Powles, Thomas; Recine, Federica; Harshman, Lauren C.; Chowdhury, Simon; Niegisch, Guenter; Yu, Evan Y.; Pal, Sumanta K.; et al.
Abstract: Background: Radical cystectomy (RC) and radiochemotherapy (RCT) are curative options for muscle-invasive bladder cancer (MIBC). Optimal treatment strategy remains unclear in elderly patients. Material and methods: Patients aged 80 years old and above with T2-T4aN0-2M0-Mx MIBC were identified in the Retrospective International Study of Cancers of the Urothelial Tract (RISC) database. Patients treated with RC were compared with those treated with RCT. The impact of surgery on overall survival (OS) was assessed using a Cox proportional hazard model. Progression included locoregional and metastatic relapse and was considered a time-dependent variable. Results: Between 1988 and 2015, 92 patients underwent RC and 72 patients had RCT. Median age was 82.5 years (range 80–100) and median follow-up was 2.90 years (range 0.04–11.10). Median OS was 1.99 years (95%CI 1.17–2.76) after RC and 1.97 years (95%CI 1.35–2.64) after RCT ( p  = .73). Median progression-free survival (PFS) after RC and RCT were 1.25 years (95%CI 0.80–1.75) and 1.52 years (95%CI 1.01–2.04), respectively ( p  = .54). In multivariate analyses, only disease progression was significantly associated with worse OS (HR = 10.27 (95%CI 6.63–15.91), p  < .0001). Treatment modality was not a prognostic factor. Conclusions: RCT offers survival rates comparable to those observed with RC for patients aged ≥80 years.